The Japanese version of the Rapid Dementia Screening Test is effective compared to the clock-drawing test for detecting patients with mild Alzheimer's disease - Moriyama, Yasushi; Yoshino, Aihide; Yamanaka, Kaori; Kato, Motoichiro; Muramatsu, Taro; Mimura, Masaru (Psychogeriatrics, 2016)
Background The Japanese version of the Rapid Dementia Screening Test (RDST‐J) and the clock‐drawing test (CDT) are both brief psychometric screening tools used to detect the severity of Alzheimer's disease. It remains unclear, however, which is more effective when screening for mild Alzheimer's disease. Methods We administered the RDST‐J and CDT to 250 patients with very mild to severe Alzheimer's disease and to 49 healthy volunteers. Patients with a Mini‐Mental State Examination score of 12–26 had Clinical Dementia Rating (CDR) scores from 0.5 to 3. Patients were divided into four groups according to CDR score. We performed one‐way factorial anova between the four groups and control subjects based on the CDT and RDST‐J scores. Results Data analysis revealed that RDST‐J could distinguish patients with CDR 0.5 from the controls, but CDT could not. Furthermore, the sensitivity of a RDST‐J score ≥8 was 57.1%, with a specificity of 81.0%, and the sensitivity of a RDST‐J score ≥9 was 79.6%, with a specificity of 55.1% for discriminating CDR 0.5 from controls. Conclusions RDST‐J is a more effective tool than CDT for distinguishing CDR 0.5 from controls.